Illicit Financial Flows and Trade Mispricing: Decomposing the Trade Reporting Gap - Alex Cobham; Petr Jansky; Jan Mares (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Despite a Sustainable Development Goals target to reduce trade mispricing and other illicit financial flows, it is not clear how to measure trade mispricing over time for countries worldwide. We aim to combine a broad coverage of countries by using UN Comtrade data and robustness by developing a new methodology that sheds new light on a potential scale of trade mispricing for many countries worldwide. Specifically, we provide new estimates of the trade reporting gap and, for the first time, we decompose it into seven individual components. Our explorative analysis reveals three main findings. We show, first, that trade reporting gap is large, in absolute values as well as relative to the overall trade. Second, conceptually well-defined components such as product and country misclassifications account only for a small share of trade reporting gap. The large remaining residual hints at the degree of imprecision in international trade reporting and calls for a significant improvement in data quality. Third, the low-income countries' trade reporting gap has the highest ratio relative to their GDP, which is consistent with existing literature that shows low-income countries to be more vulnerable to a variety of illicit financial flows.
Keywords: F13; F14; H26; 330; international trade; trade reporting gap; trade mispricing; illicit financial flows; low-income countries; global development